2018
DOI: 10.3390/ma11050754
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Uses and Therapeutic Advantages of Nanoparticles for Atherosclerosis Research

Abstract: Nanoparticles are uniquely suited for the study and development of potential therapies against atherosclerosis by virtue of their size, fine-tunable properties, and ability to incorporate therapies and/or imaging modalities. Furthermore, nanoparticles can be specifically targeted to the atherosclerotic plaque, evading off-target effects and/or associated cytotoxicity. There has been a wealth of knowledge available concerning the use of nanotechnologies in cardiovascular disease and atherosclerosis, in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 145 publications
0
18
0
Order By: Relevance
“…However, this concept fell out of favor after the arrival of coronary stenting and a lack of clinical results [145]. Nanoparticle approaches may provide possibilities for safe gene medication, with the goal of attenuating atherosclerosis [201] (Table 2). Silica–gold nanoparticles used for the atheroprotective management of plaques (the NANOM-FIM trial (NCT01270139)) showed a remarkable regression of coronary atherosclerosis [149].…”
Section: Potential Therapies For Promoting Plaque Regressionmentioning
confidence: 99%
“…However, this concept fell out of favor after the arrival of coronary stenting and a lack of clinical results [145]. Nanoparticle approaches may provide possibilities for safe gene medication, with the goal of attenuating atherosclerosis [201] (Table 2). Silica–gold nanoparticles used for the atheroprotective management of plaques (the NANOM-FIM trial (NCT01270139)) showed a remarkable regression of coronary atherosclerosis [149].…”
Section: Potential Therapies For Promoting Plaque Regressionmentioning
confidence: 99%
“…These nano-based systems may be prepared from either organic (such as biocompatible polymers), or inorganic (such as iron oxides) materials, although recent attempts are focused on the development of novel systems combining both [3,4,5]. Generally, nanoparticles suited for targeted cancer therapy have a particle size between 1 and 200 nanometers and, depending on the materials used and the manufacturing process employed, they may possess unique physicochemical and mechanical properties [6,7,8,9]. These properties may be tailored to meet specific requirements by altering several attributes such as nanoparticle composition, size, shape, surface morphology, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide clinical relevance and adaptability, we also incorporated gadolinium (Gd) to allow for simultaneous molecular magnetic resonance (MR) imaging of plaques. We chose MR imaging specifically as it is a noninvasive imaging modality capable of producing high‐resolution images, without the use of ionizing radiation that are characteristic to angiography, computed tomography (CT), and positron emission tomography (PET) . Moreover, although near‐infrared fluorescence (NIRF) imaging is popular for small animal imaging, NIRF imaging alone is hindered by poor tissue penetration and high tissue autofluorescence, making it difficult for transition into the clinic .…”
Section: Introductionmentioning
confidence: 99%
“…We chose MR imaging specifically as it is a noninvasive imaging modality capable of producing high-resolution images, without the use of ionizing radiation that are characteristic to angiography, computed tomography (CT), and positron emission tomography (PET). [22][23][24][25][26][27] Moreover, although near-infrared fluorescence (NIRF) imaging is popular for small animal imaging, NIRF imaging alone is hindered by poor tissue penetration and high tissue autofluorescence, making it difficult for transition into the clinic. [28] Gd is an FDA-approved contrast agent that produces contrast-enhanced MR images with high signal-to-noise ratio (SNR), which makes it favorable for use in nanoparticle platforms.…”
Section: Introductionmentioning
confidence: 99%